Edukasi Pemanfaatan Teknologi Carbon Capture Storage untuk Mitigasi Gas Rumah Kaca di SMK Migas Bumi Melayu Riau - Muhammad Ariyon; Ellyan Sastraningsih; Fitrianti Fitrianti; Thoriq Nibras (PELANTAR PRESS, 2026)
Mitigating greenhouse gas (GHG) emissions in the energy sector requires early capacity building through vocational education, particularly in oil and gas disciplines. Carbon Capture and Storage (CCS) is a key technology supporting the energy transition, yet its educational implementation at vocational high schools remains limited. The novelty of this Community Service Program (PKM) lies in developing a CCS educational model specifically tailored to oil and gas vocational schools, integrating industry-oriented learning, Indonesian oil and gas case studies, and climate mitigation perspectives. This program aims to improve the literacy, understanding, and environmental awareness of students and teachers at SMK Migas BMR Pekanbaru regarding CCS as a low-carbon technology. The methods include interactive lectures, applied workshops, case-based discussions, and the development of contextual vocational learning modules. The results show improved participant understanding of CCS concepts and GHG mitigation. Program outputs include a CCS vocational module, learning media, and PKM documentation, contributing to vocational education strengthening and sustainable energy transition in Indonesia